TINJAUAN HUKUM TERHADAP PEMBATALAN PERKAWINAN ATAS DASAR PERBEDAAN ORIENTASI SEKSUAL - Zsa Zsa Quamila Pasyura; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
In principle, a marriage can be annulled. An annulment of a marriagemeans that the marriage is considered non-existent or even never existed. At thistime, many problems occur within the family sphere, such as situations where acouple has entered into a marriage.The aim of writing this decision study is tofind out how judges consider in deciding cases of marriage annulment based ondifferences in sexual orientation and what efforts can be made to prevent andanticipate the occurrence of marriage annulments on the basis of differences insexual orientation by considering 3 (three) decisions, the analysis will focus on 3(three) decisions in order to gain comprehensive insight regarding the factorsconsidered by the judge. This research is normative juridical research using anapproach to legal principles.The results of the research can be concluded that first, in the judge'sconsideration of these decisions, the judge considered the facts, legalinterpretation, and aspects of justice in annulling marriages based on differencesin sexual orientation. Decision Number 0059/Pdt.G/2018/PA.Pts was based onmoral violations and fraud, while Decision Number 981/Pdt.G/PA.Btl stated thatmarriage annulment occurred due to different sexual orientations (homosexual).Decision Number 0877/Pdt.G/2021/PA.Krs noted the failure of reconciliationthrough counseling and mediation, and concluded that the Petitioner had thecapacity to apply for marriage annulment. Second, it is important to haveprevention and anticipation to avoid marriage annulment caused by differencesin sexual orientation. In Decision Number 0059/Pdt.G/2018/PA.Pts it is based onmoral violations. Prevention efforts that can be taken include getting to know theprospective partner you are going to marry and strengthening legal protection. InDecision Number 981/Pdt.G/PA.Btl the efforts that can be made are tounderstand that marriage is an agreement or pact between a husband and wifeand God and to provide educational facilities regarding legal consequences. InDecision Number 0877/Pdt.G/2021/PA.Krs.Keywords: Annulment of Marriage, Differences in Sexual Orientation, Judge'sConsideration.